2008
DOI: 10.1158/1078-0432.ccr-08-0843
|View full text |Cite
|
Sign up to set email alerts
|

A Synovial Sarcoma-Specific Preoperative Nomogram Supports a Survival Benefit to Ifosfamide-Based Chemotherapy and Improves Risk Stratification for Patients

Abstract: Purpose:To identify prognostic factors related to outcome in 255 patients with synovial sarcoma and to construct a preoperative nomogram to predict the risk of disease-specific death. Design: Between July 1982 and June 2006, 301patients underwent treatment at our institution for primary synovial sarcoma of all anatomic sites and 255 patients with localized disease at presentation were resected with curative intent. Data were collected prospectively and analyzed retrospectively. Results: Five-, 10-, and 15-year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
146
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(152 citation statements)
references
References 24 publications
(36 reference statements)
4
146
2
Order By: Relevance
“…The efficacy and role of chemotherapy in synovial sarcoma are still uncertain [4,39,40]. A previous study reported that 5-year event-free survival was not different in patients with synovial sarcoma who received or did not receive NAC (62.6 vs. 71.5 %) [41].…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy and role of chemotherapy in synovial sarcoma are still uncertain [4,39,40]. A previous study reported that 5-year event-free survival was not different in patients with synovial sarcoma who received or did not receive NAC (62.6 vs. 71.5 %) [41].…”
Section: Discussionmentioning
confidence: 99%
“…A block of tissue allows the pathologist to examine tumor architecture and cellular interrelation, improving the diagnosis of histologic subtype and grade compared to FNA [13,19,56]. Other advantages of core biopsy, as with FNA, include speed, convenience, decreased cost (average $1106 per case), minimal morbidity, minimal contamination, and a 0.1% to 1.1% complication rate; disadvantages are also similar to FNA and include limited sampling and inaccessibility of some masses (secondary to size, depth, density, or location) [8,24,25,40,50,53,56].…”
Section: Introductionmentioning
confidence: 99%
“…Adjuvant radiotherapy has been shown to decrease rates of local recurrence; however, the role of adjuvant chemotherapy has been less clear [1, 4-6, 13, 17]. Local and distant control of certain histological subtypes of STS improves with chemotherapy; however, there are conflicting results regarding the applicability of chemotherapy to STS as a whole [3][4][5]14].…”
Section: Introductionmentioning
confidence: 99%